Audience Engagement in Lukan Framing of Petrine Speeches in Acts: Considerations for Preaching in an Asian Context - Mak, Sue Ann (2021)
This article evaluates the initial readiness, content engagement, and ensuing response of the listeners in each of Peter’s five speeches in Acts as presented from Luke’s perspective in order to examine the role of the audience in relation to the speeches. Are the Lukan Peter’s speeches shaped and influenced by the narrative audience involved? If so, in what ways and to what extent? We will observe in the five speeches whether the audience within each Lukan frame is presented as Jew or Gentile, crowd or an authoritative figure, receptive or hostile and whether Peter’s speech content manifests a particular rhetorical fit with the depicted audience. Based on these findings from Peter’s speeches, we conclude by considering some applications for preaching to audiences in Asia.
Keywords: Acts; Petrine speeches; audience; narrative frame; Preaching